Engaging Self-Reflective Learning Strategies on Virtual Classes Conduct at Higher Education Level - Diah Astuty; Lilik Uzlifatul Jannah (Sean Institute, 2022)
This study was a case study that explore the use of self-reflective learning strategies to virtual classes conduct at higher education level. The self-reflective learning strategy was in the form of student’s self-journaling. The participants of this study were ten students that divided into two groups of study. There were six female students and four male students. The instruments used in this study were interviews and observation notes on each individual student's learning journal on virtual classes.